Mengkaji dampak kondisi sosial ekonomi masyarakat nelayan terhadap moral ekonomi serta implikasinya pada perilaku ekonomi - Nurdianita Syamsu Wahidatul Afrina; Shendy Andrie Wijaya; David K Susilo (Jurnal Pendidikan Ekonomi (JUPE), 2026)
Poverty in the coastal area of ​​Puger remains a particularly problematic phenomenon. Changes in social and economic conditions impact poverty and the well-being of fishing communities. The purpose of this study is to identify the impact of social and economic conditions in fishing communities on economic morality and its implications for economic behavior. Sample data from 120 respondents were analyzed using a path analysis model. The results of the study revealed the impact of socio-economic conditions in fishing communities on economic morality and economic behavior. The results of this study indicate that social, economic, and moral conditions affect the economic behavior of Puger fishing communities in decision-making related to meeting daily needs. This means that if the socio-economic conditions of fishermen are good, especially regarding daily income, then the overall economic activities of fishing communities, based on morality, will influence behavior that reflects individuals' responses to meeting their needs.